TECHNOLOGIES FOR THE DEVELOPMENT OF STUDENT RESEARCH ACTIVITIES IN THE PROCESS OF CHEMISTRY EDUCATION - Raxmonov Sh.T. (Scholar Express Journal, 2023)
In the article, methods such as designing in the development of students' research activities in the process of chemistry education, directing students from chemistry to research activities in the radical reform of the chemistry education system by creating problem situations, forming a scientific outlook in students during research activities , issues of creativity development are highlighted
Keywords: research; research - competition; learning experience; creative tasks